Effect of tool geometry on friction stir processing and fatigue strength of MIG T welds on Al alloys - Jesus, J. S. de (2014)
Several tool geometries were developed and their effect on weld morphology, material flow, microstructure and hardness of processed regions was analyzed. Their effect on fatigue strength of welds was also examined for the most promising tools. The feasibility of FSP MIG T welds was proved. Quality of processed regions is very influenced by tool geometry. FSP removes defects in the MIG weld toe and increases its radius of curvature. Also promotes significant grain refinement in processed regions, reduces hardness in welds on AA 6082-T651 and hardens AA 5083-H111 welds. Only tools with concave and rounded edge shoulder and cylindrical threaded pin allow the improvement of fatigue strength of MIG welds on both alloys.